IUTAM Symposium on Computational methods in contact mechanics Proceedings of the IUTAM Symposium held in Hannover, Germany, November 5-8, 2006 - Wriggers, Peter. (Springer Netherlands, 2007)
Multigrid Methods for Unilateral Contact Problems with Friction -- Contact Dynamics with Lagrange Multipliers -- Some Advances in Mathematical Programming Method for Numerical Simulation of Contact Problems -- Finite Element Analysis of Nonsmooth Frictional Contact -- Energy-Momentum Conserving Schemes for Frictionless Dynamic Contact Problems -- Symmetrization of Various Friction Models Based on an Augmented Lagrangian Approach -- Adaptive BEM for Contact Problems with Friction -- Recent Extensions of Mortar-Based Contact Formulations: Lubrication Modeling and Parallel Implementations -- A Coupled Contact and Decohesion Analysis of Laminated Beams -- Smooth Frictional Contact between Beams in 3D -- Nonlinear Boundary Problems for a Cylinder -- Evolution from the Hertzian Contact Model to Non-Hertzian Conditions for Fast Dynamic Simulations -- A Fully Implicit Approach for the Numerical Treatment of Tractive Rolling -- A Study on 3D Contact of Rough Surfaces Considering Finite Elastoplasticity -- Frictional Contact for Pile Installation -- The Influence of Contact Pressure on the Dynamic Friction Coefficient in Cylindrical Rubber-Metal Contact Geometries -- Modular Modelling of Dynamic Systems with Elastomer Contacts -- Two FEM Approaches for the Prediction and Quantification of “Stick-Slip” Phenomena on Rubber-Metal Sliding Contacts -- Contact Mechanics of Wearing out Solids -- Modelling of Grain Boundaries Contact in Metals -- Segregation of Particulate Material Using the Discrete Element Method -- Unilateral Contact and Damage Analysis in Masonry Arches -- Discontinuous Numerical Analysis of Masonry Vaults.